Verapamil inhibits tumor progression of chemotherapy-resistant pancreatic cancer side population cells - Zhao, Lu; Schwarz, Bettina (International journal of oncology, 2016)
Tumor side population (SP) cells display stem-like properties that can be modulated by treatment with the calcium channel blocker verapamil. Verapamil can enhance the cytotoxic effects of chemotherapeutic drugs and multi-drug resistance by targeting the transport function of the P-glycoprotein (P-gp). This study focused on the therapeutic potential of verapamil on stem-like SP tumor cells, and further investigated its chemosensitizing effects using L3.6pl and AsPC-1 pancreatic carcinoma models. As compared to parental L3.6pl cells (0.9±0.22%), L3.6pl gemcitabine-resistant cells (L3.6plGres) showed a significantly higher percentage of SP cells (5.38±0.99%) as detected by Hoechst 33342/FACS assays. The L3.6plGres SP cells showed stable gemcitabine resistance, enhanced colony formation ability and increased tumorigenicity. Verapamil effectively inhibited L3.6plGres and AsPC-1 SP cell proliferation in vitro. A pro-apoptotic effect of verapamil was observed in L3.6pl cells, but not in L3.6plGres cells, which was linked to their differential expression of P-gp and equilibrative nucleoside transporter-1 (ENT-1). In an orthotopic pancreatic cancer mouse model, both low and high dose verapamil was shown to substantially reduce L3.6plGres-SP cell tumor growth and metastasis, enhance tumor apoptosis, and reduce microvascular density.